An open-label study of quetiapine for delirium - Maneeton B. (2014)
Objective: To evaluate the effects of quetiapine treatment in patients with delirium. Material and Method: All patients with delirium were assessed. The diagnosis of delirium was confirmed by using the Confusion Assessment Method (CAM). Quetiapine at the dose between 25 and 100 mg /day was given for 7 days. The efficacy of quetiapine on delirium was evaluated by using the Delirium Rating Scale (DRS) and the Clinical Global Impression-Severity scale (CGI-S). The extrapyramidal side effects were assessed by using the Modified (9-item) Simpson-Angus Scale (MSAS). Results: Twenty-two patients had delirium. Seventeen (10 males and 7 females) subjects with a mean age (SD) of 55.6 (18.6) years were included in the present study. Means (SDs) dose and duration (SD) of quetiapine treatment were 45.7 (28.7) mg/day and 6.5 (2.0) days, respectively. The DRS and CGI-S scores of days 2-7 were significantly lower than those of day 0 (p < 0.001) for all comparisons). Only two subjects were shown to have mild tremor. Conclusion: Quetiapine within the range of 25-100 mg/day improves delirious condition within 24 hours of treatment. It is well-tolerated and has a very low propensity to induce extrapyramidal side effects. Further randomized, placebo-controlled trials are warranted.